Keterlibatan Politik ‘Aisyiyah dalam Advokasi Sosial - Alya Khoirun Nisa; Sulton Sulton; Sunarto Sunarto (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Women's political involvement is an important aspect in promoting equitable social change, but unfortunately, political involvement in Indonesia is still relatively low due to a patriarchal culture and a lack of political party support. This study aims to analyze the forms of political involvement carried out by 'Aisyiyah in promoting social advocacy. The main focus of this study includes strategies, actors, and political participation spaces used by 'Aisyiyah in fighting for the interests of society, especially vulnerable groups. This research method uses a qualitative approach through a literature review of various relevant journals, reports, and articles. The data analysis technique in this study uses coding the results of the article review analysis, then grouped based on research variables and continued with drawing conclusions based on the data analysis variables used. The research findings show that 'Aisyiyah is actively involved in social advocacy through formal and informal political channels, and utilizes the power of organizational networks and religious values to strengthen its influence. 'Aisyiyah's political participation not only reflects women's collective awareness but also serves as an instrument in shaping social policies that are responsive to community needs. This study is expected to contribute to broadening understanding of the strategic role of women's organizations in the political and social arena.